Study of B- → DK-π+π- and B- → Dπ-π+π- decays and determination of the CKM angle γ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We report a study of the suppressed B−→DK−π+π− and favored B−→Dπ−π+π− decays, where the neutral D meson is detected through its decays to the K∓π± and CP -even K+K− and π+π− final states. The measurement is carried out using a proton-proton collision data sample collected by the LHCb experiment, corresponding to an integrated luminosity of 3.0 fb−1. We observe the first significant signals in the CP -even final states of the D meson for both the suppressed B−→DK−π+π− and favored B−→Dπ−π+π− modes, as well as in the doubly Cabibbo suppressed D→K+π− final state of the B−→Dπ−π+π− decay. Evidence for the suppressed decay B−→DK−π+π−, with D→K+π−, is also presented. From the observed yields in the B−→DK−π+π−, B−→Dπ−π+π− and their charge conjugate decay modes, the most probable value of the weak phase γ corresponds to γ=(74+20−19)°. This is one of the most precise single-measurement determinations of γ to date.
Im Titel sind "-" und "+" hochgestellt
Gesehen am 02.08.2021
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]